Juger d’après les apparences : le cas du français - Alain Delplanque (Corela)
In French, the idea of appearance can be expressed in various ways, in particular with “sembler, avoir l’air, ressembler, faire”. I have tried to account for the semantic and syntactic differences between these verbs in the perspective of the “Théorie des Opérations Prédicatives et Énonciatives”. I have proposed to represent each of these verbs through a specific lexis pattern, from which all the distributional proprieties can be calculated. More precisely, each pattern corresponds to a specific ponderation between the parameters of enunciation. Thus, the notional domain of the whole sentence can be characterized in terms of discreet / dense / compact topology.